Visible-light-mediated hydrodehalogenation and Br/D exchange of inactivated aryl and alkyl halides with a palladium complex. Issue 10 (5th April 2019) - Zhou, Zhao-Zhao; Zhao, Jia-Hui; Gou, Xue-Ya; Chen, Xi-Meng; Liang, Yong-Min
Abstract : Photo-induced radical reductive dehalogenation of inactivated aryl/alkyl bromides and chlorides with a palladium complex is described. Reductive cyclization, dehalogenative deuteration, and radical addition process can be achieved smoothly. Abstract : Herein, a novel photo-induced amine-free radical reductive dehalogenation of inactivated aryl/alkyl bromides and chlorides with a palladium complex is described, which reveals excellent functional group compatibility and broad substrate scope. Extensional transformations for reductive cyclization, dehalogenative deuteration, and intra- and intermolecular radical addition can be achieved smoothly. Mechanistic studies indicate a single-electron photoredox catalytic system with inactivated solvent as the hydrogen atom donor.